Pepujian Berbahasa Jawa-Arab : Kajian Sosiolinguistik - Jihan, Aqmal; Prembayun Miji Lestari (Kawruh: Journal of Language Education, Literature and Local Culture, 2024)
Javanese-Arabic is closely related to the praise that is often chanted in villages throughout the island of Java. The chanting is inseparable from the very rapid spread of Islam in the archipelago in ancient times. The diversity of society that easily accepts outside society makes Islam and its culture mixed with local culture including language which makes it more varied. This study aims to determine the patterns and characteristics of Javanese-Arabic praise. This study uses a qualitative method with a sociolinguistic approach. The research method used is the listening and speaking method. This research was conducted in Tepus Hamlet, Magelang Regency. The data collection technique used the note and record technique. The data obtained were in the form of notes from documents and recordings of Javanese-Arabic praise. Data analysis used Miles and Huberman data analysis. The results of this study found various patterns in Javanese-Arabic praise, namely the opening and core as well as the structural patterns in the praise. The second result is that the characteristics found in this praise are greeting words such as dhuh Gusti, Tuan, Pangeran, Panjenengan, Dzat and also words that often appear are nyuwun as a context for asking Allah SWT such as dhuh Gusti kula nyuwun sehat manah lan raga. namely Asking for health of soul and body.